Determining Wages : The Changing Role of Education - Raleigh, Jacob (My University, 2014)
The purpose of this study was to take a detailed look at the determinants of wages in the U.S. and how they have changed over the last 40 years, especially focusing on the factors of education level, gender, and race.
Color poster with text and graphs.
Keywords: Labor economics; Wages--United States--History; Level of Education; Posters